ONN-complexes of dioxomolybdenum(VI) with 2-hydroxy-1-naphthaldehyde S-ethyl-4-H/phenyl-thiosemicarbazones: Crystal structure, electrochemistry and in situ spectroelectrochemistry - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Neutral dioxomolybdenum(VI) complexes of dibasic 2-hydroxy-1-naphthaldehyde S-ethyl-4-H/phenyl-thiosemicarbazones (H: L-1, C6H5: L-2) have been synthesized. The complexes. [MoO2L1(ROH)] (1a-d) and [MoO2LII(ROH)] (2a-d) (R: CH3, C2H5, C3H7, C4H9) were characterized by elemental analysis, electronic. IR and H-1 NMR spectra. X-ray crystal studies indicated a distorted octahedral geometry for [MoO2(L-1)(C2H5OH)] (1b) and [MoO2(L-2)(CH3OH)] (2a). The Mo-O bond lengths of the MoO22+, moieties are almost the same in the monoclinic crystal structures of complexes 1b and 2a, and the MoO2 cores have a cis-dioxomolybdenum structure with angles ca. 105 angstrom While 1b crystallizes in the space group C2/c, 2a crystallizes in the space group P2(1)/n. The electrochemical behaviors of the ligands and their complexes 1b and 2a were studied using cyclic voltammetry and square wave voltammetry. The half-wave potentials (E-1/2) are significantly influenced by the central metal ions, the nature of the substituents on the thiosemicarbazones, and the electronic character of the ligands, which are the important factors that control redox potentials. In situ spectroelectrochemical studies were employed to determine the spectra of the electrogenerated species of the complexes and to assign the redox processes. The colors of the electrogenerated species were determined with in situ electrocolorimetric measurements. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Thiosemicarbazone; Dioxomolybdenum complex; Structural analysis; Cyclic voltammetry; Spectroelectrochemical analysis; THIOSEMICARBAZIDE-BASED LIGANDS; TRANSITION-METAL-COMPLEXES; CIS-DIOXOMOLYBDENUM(VI) COMPLEXES; MOLYBDENUM(VI) COMPLEXES; REDOX PROPERTIES; OXO COMPLEXES; SALICYLALDEHYDE; MONONUCLEAR; DINUCLEAR; OXOMOLYBDENUM(IV)